Efektivitas Pengelolaan Alokasi Dana Desa Pada Desa Silondou Kecamatan Basi Dondo Kabupaten Tolitoli - Hilmi Hilmi; Ramlawati Ramlawati (Fakultas Ekonomi Universitas Indonesia Timur, 2020)
This research is purpose to understand (1) the effectiveness management village funds allocation in Silondou village in years 2014-2019, (2) obstacles that faced in realization village funds allocation in Silondou village, (3) cope with the obstacles in realization village funds allocation in Silondou village.The design is descriptive research. Data were collected with the documentation and interview.The result showed (1) management effectiveness village funds allocation from years 2009-2014 referring to be in category effective. The effectiveness management village funds allocation in Silondou villages year 2014 (98,98%), 2015 (100%), 2016 (100%), 2017 (98,24%), 2018 (100%), and 2019 (99,57%). (2) obstacles experienced in realization Silondou village funds allocation is the comprehension of human resources remain low, miss communication, and liquefaction the village funds allocation late. (3) cope the obstacles of realization village funds allocation can did with choacing, increase coordination, and make fund reseve.